Building an Inclusive Classroom: Emotional Disturbance and Gender Diversity in Elementary Schools - Dwiprabowo, Risky; Maksum, Arifin; Supena, Asep; Nurhasanah, Nina; Bintoro, Totok; Faujiah, Evi (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study aims to explore the challenges and strategies in creating inclusive classrooms that are friendly to students with emotional disorders and diverse gender identities in elementary schools. Using a descriptive qualitative method, this study involved 35 teachers in an inclusive primary school in East Jakarta, with data collected through a questionnaire that included aspects of challenges, positive influences of multicultural education, and inclusive strategies. The results of the study show that teachers face several key challenges, such as limited resources, understanding, and communication. However, multicultural education has been shown to improve students' empathy, tolerance, and social skills. Effective inclusive strategies include curriculum adaptation, teacher training, and collaboration with parents. Teachers also reported the positive impact of inclusive education on student attitudes and learning outcomes, including increased self-confidence, social responsibility, and collaboration skills. These results underscore the importance of adequate resource support and training programs for teachers to strengthen the effectiveness of inclusive education in primary schools. In addition, anti-stigma and diversity education programs can help reduce discrimination and increase student and public understanding of the importance of inclusion. Closer collaboration between schools and parents is also needed to create ongoing support for students with special needs.